The ClpXP protease and the ClpX unfoldase control virulence, cell division, and autolysis in Streptococcus pneumoniae - Viktor H. Mebus; Supradipta De; Larissa M. Busch; Manuela Gesell Salazar; Rabea Schlüter; Uwe Völker; Sven Hammerschmidt; Dorte Frees (Microbiology Spectrum)
ABSTRACT In all living cells, molecular chaperones and ATP-dependent proteases are essential for protein homeostasis. The ClpXP protease is a chaperone-protease complex conserved between bacteria and mitochondria. Proteolytic activity resides in the caseinolytic protease (ClpP) subunits that associate to form a tetradecameric serine protease that degrades substrates recognized and unfolded by the ClpX ATPase. In the important human pathogen Streptococcus pneumoniae (Spn), ClpX but not ClpP was proposed to be essential for viability. We here follow up on this finding by characterizing phenotypes associated with depriving S. pneumoniae D39V of ClpX unfoldase or ClpXP activity. Virulence was examined in the Galleria melonella infection model and was found to be severely attenuated for both mutants, suggesting that ClpXP is essential for virulence. Inactivation of ClpXP also resulted in elevated extracellular levels of LytA and early onset of LytA-dependent autolysis, aberrant localization of teichoic acids, and diminished cell size, while depletion of ClpX resulted in defective division septa, heterogeneous cell sizes, elongated cell chains, and cell lysis. Accordingly, proteomic analysis revealed that ClpXP directly or indirectly controls proteins involved in teichoic acid synthesis and cell division and elongation. In summary, we show that ClpX alone and in complex with ClpP control critical processes such as virulence and cell division.IMPORTANCEThe human nose is colonized by the opportunistic pathogenic bacterium Spn, a leading cause of community-acquired pneumonia and a common cause of meningitis and sepsis. In Spn, the highly conserved ClpP protease is essential for virulence, and we here show that ClpP controls virulence through associating with the ClpX unfoldase. The essentiality of Spn ClpX has hampered its characterization. By constructing Spn mutants expressing a variant of ClpX that cannot interact with ClpP, we further show that the ClpXP protease controls vital processes such as cell size and autolytic activity. Depletion of ClpX resulted in even more severe phenotypes, suggesting that ClpX unfoldase activity independently of ClpP plays a more fundamental role in coordinating cell division and cell elongation. In summary, the presented work adds to our understanding of how a highly conserved chaperone-protease complex contributes to the growth and pathogenicity of a prominent bacterial pathogen.